2014
DOI: 10.1016/j.foodchem.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa L. – A phytochemical and pharmacological review

Abstract: Hibiscus sabdariffa L. (Hs, roselle; Malvaceae) has been used traditionally as a food, in herbal drinks, in hot and cold beverages, as a flavouring agent in the food industry and as a herbal medicine. In vitro and in vivo studies as well as some clinical trials provide some evidence mostly for phytochemically poorly characterised Hs extracts. Extracts showed antibacterial, anti-oxidant, nephro- and hepato-protective, renal/diuretic effect, effects on lipid metabolism (anti-cholesterol), anti-diabetic and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
582
2
45

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 715 publications
(649 citation statements)
references
References 160 publications
20
582
2
45
Order By: Relevance
“…It is cultivated in many tropical and subtropical areas of Africa, Asia and Central America (Morton, 1987). The calices of this plant are appreciated for their use in beverages, syrups, jams and concentrates (Cissé et al, 2009;Costa-Rocha et al, 2014). The resulting products have an interesting acidity and a bright red color due to the presence of anthocyanins especially delphinidin and cyanidin 3-D-sambubioside (Chang et al, 2012;Cissé et al, 2009;Idham et al, 2012;Março et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is cultivated in many tropical and subtropical areas of Africa, Asia and Central America (Morton, 1987). The calices of this plant are appreciated for their use in beverages, syrups, jams and concentrates (Cissé et al, 2009;Costa-Rocha et al, 2014). The resulting products have an interesting acidity and a bright red color due to the presence of anthocyanins especially delphinidin and cyanidin 3-D-sambubioside (Chang et al, 2012;Cissé et al, 2009;Idham et al, 2012;Março et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although all species were collected in the same period, OE species were probably not at their optimum ripeness. Despite the fact that OE has higher content in carbohydrates and lower sugar content compared to OG and OS, this could indicate that the majority of the carbohydrates could be fibres or longer polysaccharide chains like mucilage (Da-Costa-Rocha, Bonnlaender, Sievers, Pischel, & Heinrich, 2014). This hydrocolloid, forms molecular networks that are able to retain large amounts of water, which may slow down the absorption of glucose, cholesterol and biliary salts by increasing the viscosity of food in the gut (Del Socorro-Santos-Diáz, Barba De La Rosa, Héliès-Toussaint, Guéraud, & Nègre-Salvayre, 2017).…”
Section: Hydrophilic and Lipophilic Compoundsmentioning
confidence: 99%
“…The results showed an increase in serum prolactin level and milk production in lactating female albino rats, which confirms the lactogenic property of Hibiscus sabdariffa. Studies have shown that Roselle tea contains an enzyme inhibitor which blocks production of amylase and it is possible that drinking a cup of hibiscus tea after meals can reduce the absorption of dietary carbohydrates and assist in weight loss [42]. It was also reported that Roselle is considered as a possible anti-obesity agent [43].…”
Section: Anti-oxidant Effectmentioning
confidence: 99%